Race and ethnicity and pharmacy dispensing of SGLT2 inhibitors and GLP-1 receptor agonists in type 2 diabetesResearch in context - Luis A. Rodriguez; Holly Finertie; Romain S. Neugebauer; Bennett Gosiker; Tainayah W. Thomas; Andrew J. Karter; Lisa K. Gilliam; Caryn Oshiro; Jaejin An; Gregg Simonson; Andrea E. Cassidy-Bushrow; Sarah Dombrowski; et al. (Elsevier, 2024)
Summary: Background: Sodium-Glucose Cotransporter 2 Inhibitors (SGLT2i) and Glucagon-Like Peptide-1 Receptor Agonists (GLP-1 RA) improve cardiorenal outcomes in patients with type 2 diabetes. Equitable use of SGLT2i and GLP-1 RA has the potential to reduce racial and ethnic health disparities. We evaluated trends in pharmacy dispensing of SGLT2i and GLP-1 RA by race and ethnicity. Methods: Retrospective cohort study of patients (≥18 years) with type 2 diabetes using 2014-2022 electronic health record data from six US care delivery systems. Entry was at earliest pharmacy dispensing of any type 2 diabetes medication. We used multivariable logistic regression to evaluate the association between pharmacy dispensing of SGLT2i and GLP1-RA and race and ethnicity. Findings: Our cohort included 687,165 patients (median 6 years of dispensing data; median 60 years; 0.3% American Indian/Alaska Native (AI/AN), 16.6% Asian, 10.5% Black, 1.4% Hawaiian or Pacific Islander (HPI), 31.1% Hispanic, 3.8% Other, and 36.3% White). SGLT2i was lower for AI/AN (OR 0.80, 95% confidence interval 0.68-0.94), Black (0.89, 0.86-0.92) and Hispanic (0.87, 0.85-0.89) compared to White patients. GLP-1 RA was lower for AI/AN (0.78, 0.63-0.97), Asian (0.50, 0.48-0.53), Black (0.86, 0.83-0.90), HPI (0.52, 0.46-0.57), Hispanic (0.69, 0.66-0.71), and Other (0.78, 0.73-0.83) compared to White patients. Interpretation: Dispensing of SGLT2is, and GLP-1 RAs was lower in minority group patients. There is a need to evaluate approaches to increase use of these cardiorenal protective drugs in patients from racial and ethnic minority groups with type 2 diabetes to reduce adverse cardiorenal outcomes and improve health equity. Funding: Patient-Centered Outcomes Research Institute and National Institutes of Health.